2013
DOI: 10.3382/ps.2013-03133
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preincubation heating of broiler hatching eggs during storage, flock age, and length of storage period on hatchability

Abstract: The effects of heating of eggs during storage, broiler breeder age, and length of egg storage on hatchability of fertile eggs were examined in this study. Eggs were collected from Ross 344 male × Ross 308 broiler breeders on paper flats, held overnight (1 d) at 18°C and 75% RH, and then transferred to plastic trays. In experiment 1, eggs were obtained at 28, 38, and 53 wk of flock age. During a further 10 d of storage, eggs either remained in the storage room (control) or were subjected to a heat treatment reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 14 publications
4
12
1
1
Order By: Relevance
“…These results are in correspondence with Petek and Dikmen (2006) who elucidated that there were significant pre-storage incubation × egg storage interactions (P < 0.001) for the apparent fertility, hatchability of total and fertile eggs. Also, results of the present study revealed that pre-storage incubation for 6 or 8 h had a positive effect on hatchability of set eggs and hatchability of fertile eggs and these results are in agreement with several previous studies (Petek and Dikmen, 2004;Silva et al, 2008;Gucbilmez et al, 2013). Fasenko et al (2001b) showed that the pre-storage incubation treatment of 6 h improved hatchability (81.9%) in comparison with the control treatment (72.2%) when eggs were stored for 14 days.…”
Section: Fertility and Hatchabilitysupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in correspondence with Petek and Dikmen (2006) who elucidated that there were significant pre-storage incubation × egg storage interactions (P < 0.001) for the apparent fertility, hatchability of total and fertile eggs. Also, results of the present study revealed that pre-storage incubation for 6 or 8 h had a positive effect on hatchability of set eggs and hatchability of fertile eggs and these results are in agreement with several previous studies (Petek and Dikmen, 2004;Silva et al, 2008;Gucbilmez et al, 2013). Fasenko et al (2001b) showed that the pre-storage incubation treatment of 6 h improved hatchability (81.9%) in comparison with the control treatment (72.2%) when eggs were stored for 14 days.…”
Section: Fertility and Hatchabilitysupporting
confidence: 93%
“…Similarly, Reijrink et al (2010b) showed that pre-storage incubation decreased embryonic mortality during the first 2 days of incubation by 0.8% (P = 0.01) and decreased embryonic mortality on day 20 of incubation by 0.3% (P = 0.05). These results are consistent with the findings of Fasenko et al (2001a and2001b), Reijrink et al (2009) and Gucbilmez et al (2013) who explained that pre-storage incubation enhanced the embryo viability, decreased the embryonic mortality and increased the hatchability. Gucbilmez et al (2013) reported that hatchability of fertile eggs obtained from a 29-week-old flock stored for 11 days was increased by heating at either 1 or 5 days of storage, with an accompanying significant decrease in early dead and numerical decrease in late dead as compared with the control.…”
Section: Embryonic Mortalitysupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, Marandure et al (2012) exposed broiler breeder eggs to 4 , 8 , 12 h warming , they found that hatchability decreased with time . This was not observed by Gucbilmez et al (2013) who reported no benefit effect of heating broiler breeder's eggs for 1 d of a 6-d storage period on hatchability percentage, although the storage periods by pre-heating interaction effect was significant on both hatchability and chick weight at hatch. Effect of short period incubation fourth time (2.5 and 5 h) and prolonged egg storage (21 days) on hatchability characteristics, embryonic mortality, pips and abnormal chicks:…”
Section: Fertility (%) = × 100mentioning
confidence: 61%
“…Therefore, it regularly happens that eggs from two or three different flocks are combined in one machine, which can lead to sub-optimal results. For instance, putting eggs from a flock with an age of 30 weeks with those from another flock of 60 weeks of age in the same incubator will certainly lead to a decrease in the number of hatched chicks, poorer chick quality, higher post-hatch mortality, etc., under present conditions where all eggs in the machine are treated equally [8][9][10].…”
Section: Introductionmentioning
confidence: 99%